Unusual Local Recurrence with Distant Metastasis after Successful Endoscopic Submucosal Dissection for Colorectal Mucosal Cancer - Hyo Jeong Lee; Byong Duk Ye; Jeong-Sik Byeon; Jihun Kim; Young Soo Park; Yong Sang Hong; Yong Sik Yoon; Dong-Hoon Yang (Korean Society of Gastrointestinal Endoscopy, 2017)
Intramucosal colorectal cancer (CRC) is thought not to metastasize because the colonic lamina propria lacks lymphatics. Only a few recent case reports have suggested lymph node metastasis from intramucosal CRC, but there is no clear evidence supporting the metastatic potential of intramucosal CRC. Hence, endoscopic resection is regarded as curative treatment for intramucosal CRC. This report describes two cases of unusual local recurrence with distant metastasis in patients who had previously undergone successful endoscopic submucosal dissection for intramucosal CRC. The recurrent colorectal lesions developed at the site of the previous endoscopic submucosal dissection scars in a relatively short-term period, and the pathologic findings showed an "undermining" invasion pattern without surrounding mucosal change. Based on the clinical course and pathological findings, we concluded that the second colorectal lesions were recurrences rather than de novo cancers.